2009
DOI: 10.1002/micr.20610
|View full text |Cite
|
Sign up to set email alerts
|

A novel rabbit model for the evaluation of retrograde flow venous flaps

Abstract: Venous flaps have several potential advantages over traditional flaps, but their uses have been limited by unpredictable survival. Although clinical and experimental studies have concentrated mainly on the antegrade arterialization of venous flaps to increase survival, retrogradely arterialized venous flaps (AVFs) may have the greatest potential. There is, however, little literature on their use. There are also no animal studies comparing their survival to other venous flaps used in a similar situation. Our ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Although the exact mechanism of successful tissue perfusion in AVFs is unclear, various clinical and experimental studies have confirmed skin flap survival using this unconventional technique4571016171819. AVFs may be harvested in a wide range of locations.…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact mechanism of successful tissue perfusion in AVFs is unclear, various clinical and experimental studies have confirmed skin flap survival using this unconventional technique4571016171819. AVFs may be harvested in a wide range of locations.…”
Section: Discussionmentioning
confidence: 99%
“…However, this technique remains unreliable, complicated by full‐thickness necrosis, postoperative bulkiness, and venous congestion 2. 51…”
Section: Modifications To Flap Designmentioning
confidence: 99%
“…Several experimental studies and clinical applications have been performed to evaluate whether different surgical procedures could enhance flap perfusion and flap survival. 2,415 These experimental procedures include increasing angiogenesis by flap preexpansion, 4,7,8 prearterialization technique, 4,9,10 and surgical and pharmacological flap delay procedures. 2,4,11,1620 These procedures have been used successfully to increase flap blood flow and tissue oxygenation.…”
mentioning
confidence: 99%
“…24,13,25,27,2933 Composite flaps have been used for reconstruction of nerves, vessels, and tendons, 13,21,3437 while AVFs have also been used in reconstruction of small hand defects. Small-sized AVFs (1 × 1 cm up to 3 × 10 cm) have a 95–100% survival rate.…”
mentioning
confidence: 99%
See 1 more Smart Citation